An overview of counselor ethical code and ethical principles in Malaysian setting - Mat Rani, Nurul Hasyimah; Wan Jaafar, Wan Marzuki; Mohd Noah, Sidek; Mohd Jais, Samsiah; Bistamam, Mohammad Nasir (Human Resource Management Academic Research Society, 2017)
Counselors are increasingly needed not only in public institutions and private but also in the events of natural disaster and tragedy in the country such as the tsunami on 26 December 2004, a major flood in Kelantan in 2014, also MH370 and MH17 crash incidents in December 2014. Counselors also work with various groups such as children, school-going students, people with disabilities, single mothers, teenagers, university students, parents, spouses, and workers. As someone who delivers a professional service, counselors should offer their services in an ethical manner and avoid an unethical behavior. Ethical code and ethical principles can guide counselors in practicing counseling services in an ethical manner. This paper gives an overview about the Board of Counselor (Malaysia), the goals and sections in the Code of Ethics in the Malaysian setting and ethical principles in counseling practices. The main objective of this paper is to apply the code of ethics and ethical principles in solving ethical issues. The impending conclusion and implication will also be discussed.